THE EFFECT OF BASIC MOTOR ABILITIES ON DRIBBLING SPEED AND PRECISION IN SOCCER GAME - Ismail Selimović; Mehmeti Ejup (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Effects of basic motor skills on situational-motor abilities for speed dribble and ball control precision assessment in soccer game at boys aged 12-14 years were analyzed with regression analysis. For this purpose, 17 variables for basic motor parameters were selected, as well as three situational tests. In every example of the regression analysis results, the results obtained showed confirmation of the hypothesis of significant effects of the morphological characteristics on the results in analyzed situational- motor tests.